In-vitro bioactivity evaluation and physical properties of an epoxy-based dental sealer reinforced with synthesized fluorine-substituted hydroxyapatite, hydroxyapatite and bioactive glass nanofillers - Jerri Al-Bakhsh, Bahaa Abdulrazzaq (Bioact Mater, 2019)
The purpose of this study was to evaluate the physical properties and bioactivity potential of epoxy-based dental sealers modified with synthesized bioactive glass (BAG), hydroxyapatite (HA) and fluorine substituted hydroxyapatite (FHA) nanoparticles. The synthesized powders were incorporated at 10% and 20% into the epoxy-based dental sealer. The setting time, flow and solubility and microhardness of the modified and unmodified samples were examined. The bioactivity was evaluated using FESEM-EDX and elemental mapping, ATR-FTIR and XRD. The flow value of all of the experimental groups except the FHA modified samples, was greater than 20 mm. Concerning solubility, no specimens exhibited more than 1% weight loss. The solubility value of the FHA groups was statistically significant lower than other groups (p ≤ 0.001). The mean hardness values of all of the modified samples were significantly higher than the unmodified group (p ≤ 0.001). Regarding bioactivity, in vitro study revealed that after 3 days immersion in SBF a compact and continuous calcium phosphate layer formed on the surface of epoxy sealers containing BAG and HA nanoparticles. Based on these results, the addition of BAG and HA nanoparticles did not adversely alter the physical properties of epoxy sealers. Additionally, they improved the in vitro bioactivity of the epoxy sealer.